PERANCANGAN SISTEM KONTROL JARAK JAUH RECEIVER SATELIT MENGGUNAKAN METODE SMS BERBASIS ARDUINO NANO DI PT. IMANI PRIMA - Aan Abdullah; Nurhayati (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
This study designed a satellite receiver remote control system using the SMS method based on Arduino nano at PT. Prime Faith. The purpose of this research is to make it easier for users to control the system remotely, perform maintenance and restart the satellite receiver system easily This research emphasizes controlling the AIS receiver with the SMS module, the AIS receiver is for monitoring ships, this device can be installed throughout Indonesia. If there is damage that results in expensive maintenance, remote and others. Can be controlled using this sms system. The results of the research carried out are the sms module to control the ais receiver.